Pengaruh Manajemen Pengelolaan Pamsimas Terhadap Kepuasan Pelanggan Desa Gempolrejo Dusun Sumberjo Kecamatan Tunjungan KAB. Blora - Saryono Saryono; Amelia Anwar (Lembaga Pengembangan Kinerja Dosen, 2024)
Pamsimas is a program implemented by the government to help the community in providing drinking water and overcoming difficulties in getting clean water. This research aims to determine the influence of Pamsimas Management on Customer Satisfaction of Community-Based Drinking Water (PAMSIMAS). The Pamsimas program is one of the programs implemented by the Indonesian Government. The aim of this research is to find out about the